Pembelajaran Sosial Berbasis Tematik “Warisan Keluarga Kami” Pada Kelas VI Sekolah Alam Nurul Islam Yogyakarta - Dewi, Nesya Arantika; Rianto, Subandi (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
This research aims to examine the effectiveness of a thematic-based learning system regarding Indonesian culture and local wisdom for elementary school at Nurul Islam School Yogyakarta with observation and participatory approach. This study uses a thematic learning method which is an integration of learning from various interrelated subjects, with sub-methods including the process of observing, asking, trying, reasoning and communicating. As well as sub-methods of working together between parents and children to foster emotional closeness in the family. The result showed that the thematic-based social learning process was effective and was able to become a means for children of primary school age to know their identity as the Indonesian nation.